Sublingual immunotherapy provides long‐term relief in allergic rhinitis and reduces the risk of asthma: A retrospective, real‐world database analysis. Issue 1 (10th August 2017) - Zielen, S.; Devillier, P.; Heinrich, J.; Richter, H.; Wahn, U.
Abstract: Background: Allergy immunotherapy (AIT) is the only treatment for allergic rhinitis (AR) and/or allergic asthma (AA) with long‐term efficacy. However, there are few real‐life data on the progression of AR and/or AA in patients receiving AIT. Objectives: To assess the real‐world, long‐term efficacy of grass pollen sublingual immunotherapy (SLIT) tablets in AR and their impact on asthma onset and progression. Methods: In a retrospective analysis of a German longitudinal prescription database, AR patients treated with grass pollen SLIT tablets were compared with a control group not having received AIT. Multiple regression analysis was used to compare changes over time in rescue symptomatic AR medication use after treatment cessation, asthma medication use, and the time to asthma onset in the two groups. Results: After applying all selection criteria, 2851 SLIT and 71 275 control patients were selected for the study. After treatment cessation, AR medication use was 18.8 percentage points lower (after adjustment for covariates, and relative to the pretreatment period) in SLIT tablet group than in the non‐AIT group ( P <.001). Asthma onset was less frequent in SLIT tablet group than in non‐AIT group (odds ratio: 0.696, P =.002), and time to asthma was significantly longer (hazard ratio: 0.523; P =.003). After SLIT cessation, asthma medication use fell by an additional 16.7 percentage points (relative to the pretreatment period) in the SLIT tablet group vs the non‐AIT group ( P =.004). Conclusions: Real‐world treatment of AR patients with grass pollen SLIT tablets was associated with slower AR progression, less frequent asthma onset, and slower asthma progression.